2020
DOI: 10.1111/tbed.13325
|View full text |Cite
|
Sign up to set email alerts
|

A review of recent research on Theileria parva : Implications for the infection and treatment vaccination method for control of East Coast fever

Abstract: The infection and treatment (ITM) live vaccination method for control of Theileria parva infection in cattle is increasingly being adopted, particularly in Maasai pastoralist systems. Several studies indicate positive impacts on human livelihoods. Importantly, the first detailed protocol for live vaccine production at scale has recently been published. However, quality control and delivery issues constrain vaccination sustainability and deployment. There is evidence that the distribution of T. parva is spreadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 77 publications
0
19
0
Order By: Relevance
“…Similarly, longitudinal studies, unlike cross-sectional studies, can provide more insight into the impact of the infection and treatment method (ITM) in the control of ECF in endemic countries, like the one done in Tanzania [35]. These studies can also help to address some concerns associated with the long-term use of the MC [35,36]. Thus, there is a need to carry out longitudinal studies in Malawi to have a complete profile and impact of the MC on the population genetics of T. parva.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, longitudinal studies, unlike cross-sectional studies, can provide more insight into the impact of the infection and treatment method (ITM) in the control of ECF in endemic countries, like the one done in Tanzania [35]. These studies can also help to address some concerns associated with the long-term use of the MC [35,36]. Thus, there is a need to carry out longitudinal studies in Malawi to have a complete profile and impact of the MC on the population genetics of T. parva.…”
Section: Discussionmentioning
confidence: 99%
“…Animals treated with the ITM protocol can remain life-long carriers and can potentially spread vaccine strains into areas previously free from them. It requires a continuous cold chain in liquid nitrogen, cotreatment with oxytetracycline, skilled personnel for delivery and is laborious to produce (reviewed in 50 ). Consequently, the development of a subunit vaccine with minimal risks and easier production processes is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Despite inducing a protective immune response, ITM presents several constraints, such as high cost and complexity of the production of vaccine batches and need for a cold chain for distribution. Another downside of ITM is the establishment of persistent infection in vaccinated animals and the potential risk for tick transmission, even though recent studies showed that ITM parasites do not replace the local parasite population, which, at least in part, favors the use of ITM to mitigate acute ECF [44,45]. In addition, ITM relies on the use of oxytetracycline, which raises concerns on the spread of antibiotic resistance and contamination of food and dairy products.…”
Section: Vaccines Against Theileria Spp Of Importance To Cattlementioning
confidence: 99%